2021
DOI: 10.33448/rsd-v10i14.21758
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting of anti-Candida bioactive in Origanum vulgare L. artisanal essential oil

Abstract: Candida albicans is a yeast belonging to the normal microbiota of the human body, considered the most pathogenic species of the genus. It is the main microorganism related to candidiasis. Essential oils of Origanum vulgare have phenolic compounds, such as thymol and carvacrol, which have an effective antimycobacterial character at certain concentrations, but little is known about its biological activity in artisanal preparation. Thus, we evaluated the resistance of standard strains of opportunistic yeast C. al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…On the contrary, Abd El Tawab et al [51], who investigated the antifungal activity of seven EOs, reported resistance of C. albicans isolates to all of tested EOs. Interestingly, in the study conducted by Rocha et al [52] C. albicans was resistant to oregano EO, leading to atypical colony sizes, possibly interfering with its pathogenicity. Despite the unchanged total cell count, there was a notable decrease in whole-cell concentration and growth of non-intact cells, possibly influenced by the oil's compounds.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Abd El Tawab et al [51], who investigated the antifungal activity of seven EOs, reported resistance of C. albicans isolates to all of tested EOs. Interestingly, in the study conducted by Rocha et al [52] C. albicans was resistant to oregano EO, leading to atypical colony sizes, possibly interfering with its pathogenicity. Despite the unchanged total cell count, there was a notable decrease in whole-cell concentration and growth of non-intact cells, possibly influenced by the oil's compounds.…”
Section: Discussionmentioning
confidence: 99%